Bioethical deontological and medical-legal problems of perinatal medicine - Pascali, V. L.; Bottone, E.; Fiori, Angelo (Medicina e Morale, 1992)
The four levels (technical professional in the strict sense, legal, deontological and bioethical which the doctor-patient relationship is part of, include various problems with respect to informed consent and the serviccs for the diagnosis and treatment of diseases of the fetus and the newborn. The authors outline these problems and study them mainly from the point of view of ltalian legal and deontological regulations.